Non-targeted metabolomics reveals the taste variations during Baccaurea ramiflora Lour. fruit maturation - Yang, Chongcheng; Chen, Jiaqi; Zhang, Yang; Huang, Jianjian; Wang, Huachen; Chen, Jie (Frontiers in Plant Science, 2024)
Baccaurea ramiflora Lour. is a new kind of underutilized wild fruit tree which the metabolic reasons of its fruit flavor changes were not yet clear. In this study, the pink flesh and excellent taste fruit (BR) was used to reveal the metabolic causes of taste variations through 5 developmental stages. We identified 154 common differential metabolites of different developmental stages based on non-targeted metabolomics analysis. The accumulation of sugar and fatty acids increased significantly after 73 days, while citric acid decreased significantly. Flesh color accumulation mainly occurred 53 days ago, vitamin accumulation occurred after 93 days. Interestingly, L-sorbose and 5-hydroxyindole-3-acetic acid were positively correlated with the sugar-acid ratio, but negatively correlated with the titratable acids.It indicated that L-sorbose and 5-hydroxyindole-3-acetic acid may be taste biomarkers of BR B. ramiflora. The results provided new metabolic evidences for the taste variation during the ripening process of B. ramiflora.